Estudo da imunoexpressão dos sistemas CXCR4-CXCL12/SDF-1, CCR7-CCL21 e KI-67 no carcinoma de células escamosas oral e sua associação com indicadores clínicopatológicos, metástase linfonodal e sobrevida - Cavalcante, Galyléia Meneses (2013)
Chemokines are responsible for the directed migration of leukocyte chemotactic cytokines, coordinating cell movement during inflammation and the transport of hematopoietic cells. In addition to leukocytes, chemokine receptors are also found in neoplastic cells and tumors associated with stromal cells. Among chemokines, and the CXCR4/CXCL12 CCR7/CCL21 systems have been shown the involvement of lymph node metastases or distant metastases in different cancers. Thus, aim of this study was to evaluate the expression of CXCR4, CXCL12, CCR7, CCL21 and Ki-67 in oral squamous cell carcinoma (SCC) and to correlate these markers with clinicopathological indicators, lymph node metastasis and survival. We conducted a survey of reports and paraffin blocks of excisional biopsies of patients with SCC treated at the Hospital Haroldo Juaçaba (2001-2009). Data on anatomic location of the lesion, sex, age, patient survival, degree of histological differentiation of the tumor, tumor stage and presence or absence of lymph node metastasis, lymphovascular and perineural invasion, nuclear grade and depth of invasion were collected. For immunohistochemical analysis, followed by the technique of streptavidin-biotin-peroxidase using the anti-CXCR4, anti-CXCL12, anti-CCR7, anti-CCL21 and Ki-67 antibody. Histological sections were photomicrographed in 10 fields chosen randomly and measured for the number of labeled tumor cells and determined the percentage of each labeling antibody. The marking of CXCR4 was detected in the cytoplasm and nucleus, CXCL12, CCR7 and CCL21 were only cytoplasmic, their expression was observed in 18 (60%) 8 (22.66%) 16 (53.3%) and 3 (12%) cases, respectively. We found a significant positive association between lymphovascular invasion and immunostaining of CXCR4 (p = 0.007) and CCR7 (P = 0.01) and among these cases metastasis was present in 62.5% and 37.5%, respectively. When in combination with Ki67, we found a significant positive correlation between CXCR4 (p = 0.0086), CXCL12 (p = 0.036) and CCR7 (p = 0:04). Among patients CXCR4 + over 111 months, only 38.4% were alive (p = 0.845), whereas both patients CCR7 + (p = 0.398) as well as CXCR4 +, and CCR7 + (p = 0.441) after 62 months, everyone had already died. We conclude that these chemokines are associated with lymphovascular invasion and cell proliferation, perhaps favoring the development of metastasis and poor prognosis.